Substitution Conformation Balances the Oscillator Strength and Singlet–Triplet Energy Gap for Highly Efficient D–A–D Thermally Activated Delayed Fluorescence Emitters. Issue 11 (1st April 2019) - Wei, Xiaofang; Li, Zhiyi; Hu, Taiping; Duan, Ruihong; Liu, Jianjun; Wang, Ruifang; Liu, Yanwei; Hu, Xiaoxiao; Yi, Yuanping; Wang, Pengfei; Wang, Ying
Abstract: Four donor–acceptor–donor region isomers (2, 3‐TXO‐PhCz, 2, 6‐TXO‐PhCz, 2, 7‐TXO‐PhCz, and 3, 6‐TXO‐PhCz) are designed. The substitution positions of the two PhCz units significantly impact the photophysical properties of the isomers, especially for the singlet–triplet energy splitting (Δ E ST ) and oscillator strength ( f  ). 2, 3‐TXO‐PhCz exhibits weak emission due to the large steric hindrance of the two PhCz units. While 2, 6‐TXO‐PhCz, 2, 7‐TXO‐PhCz, and 3, 6‐TXO‐PhCz all exhibit strong emission. The four emitters possess small Δ E ST of 0.01–0.24 eV; the corresponding f values are 0.064, 0.107, 0.026, and 0.134. Consequently, the photoluminescence quantum yields (PLQYs) of the doped films in CBP host are: 62.1% for 2, 3‐TXO‐PhCz, 83.8% for 2, 6‐TXO‐PhCz, 89.0% for 2, 7‐TXO‐PhCz, and 85.4% for 3, 6‐TXO‐PhCz. Although notable divergences of f and Δ E ST exist between 2, 6‐TXO‐PhCz and 2, 7‐TXO‐PhCz, similar PLQY of doped film in the CBP host, and exciton utilization and external quantum efficiency (EQE) of the corresponding devices can be achieved: 2, 6‐TXO‐PhCz and 2, 7‐TXO‐PhCz endow the organic light‐emitting devices with high EQE of 23.2% and 24.4%. This proximity can be attributed to the synergistic effect of f and Δ E ST . This finding highlights the beneficial role of the different linking positions on the acceptor unit in facilitating the adjustment of f and Δ E ST in order to improve the device efficiency. Abstract : Different substitution positions of the acceptor unit impact the adjustment of the oscillator strength ( f ) and singlet–triplet energy gap (Δ E ST ), which facilitates the balance of photoluminescence quantum yield (PLQY) and Δ E ST . The four emitters possess small Δ E ST of 0.24, 0.20, 0.01, and 0.22 eV with excellent thermally activated delayed fluorescence (TADF) characteristics; the corresponding f values are 0.064, 0.107, 0.026 and 0.134.